Trends in Cancer Cases and Morphine Prescription at the Korle-Bu Teaching Hospital: 2011-2015. - Amankwah-Marfo, J. (University of Ghana, 2016)
A retrospective record review on cancer cases covering the period 2011 to 2015 was undertaken at the National Centre for Radiotherapy and Nuclear Medicine at the Korle Bu Teaching Hospital to determine trends in cancer cases and morphine prescriptions at the hospital. Data covering the period 2011 to 2015 were also retrieved from the cancer registry to ascertain the number of cases reported. Patients’ data including age, sex, types of cancer as well as the various stages of the cancers and prescribed medications were also retrieved. The data revealed a declining trend in reported cancer cases from 2011 to 2013. A sharp rise was however, observed from 2014 to 2015. Higher proportions of cancer cases were reported among those aged above 41 years, with more females (66.8%, 668/1000) than males reporting at the Centre. The per capita morphine consumption decreased from the beginning of the study, 22.4% in 2011, to 17.9% in 2013 but there was a sharp increase to 27.9% in 2014 and decreased gradually to 12.7% in 2015 being the end of the study respectively. In conclusion, there was an increasing trend in the reported cancer cases for the past couple of years yet the prevalence of morphine use among these patients was inconsistent and seemed virtually low. The findings could serve as the basis for further research on the reasons of the low prescriptions of morphine since there seem to be an increasing trend in cancer cases.
Thesis(MPH)-University of Ghana, 2016
Keywords: Cancer Cases; Morphine Prescription; the Korle-Bu Teaching Hospital